"We are feeling older than our age": Vulnerability and adaptive strategies of aging people to cyclones in coastal Bangladesh. (September 2020) - Malak, Md. Abdul; Sajib, Abdul Majed; Quader, Mohammad Abdul; Anjum, Humayra
Abstract: Bangladesh has been affected by the adverse impact of natural hazards such as cyclones, floods, erosion, salinity intrusion, and so on due to the changes in global climate variability. Among the environmental stressors, tropical cyclones frequently impact the coastal people of Bangladesh. This paper details a study on the vulnerability and adaptation strategies of older people in the face of cyclones in a coastal location in Bangladesh using qualitative strategy of enquiry. Field data have been collected through 32 semi-structured interviews, three focus group discussions, and three oral history in three selected villages (Lebubunia, Gabura and Dumuria) in the study area. In this research, we argue that the aged are more affected compared to an adult in a cyclone. Findings show that due to their fewer assets and dependency on young adult family members, older people experience high vulnerability in cyclone landfall. Moreover, their lesser physical strength and weakening mental capacity make them vulnerable. In the absence of appropriate essential initiatives—lack of social awareness, training, limited access to health facilities—vulnerability borders on the extreme. Often the elderly are deprived of proper sanitation and hygiene facilities, food security, and family care and support. Many also lack access to government income support. To increase older persons' adaptability to cyclone disasters, all levels of society need to pay them special attention. This necessitates government institutions, NGOs and other stakeholders working collectively to reduce the risk to and vulnerability of the aged to cyclones. An older people's agenda framework also needs to be created. Highlights: Fewer assets and dependency on young adult family members increases the older peoples' vulnerability to cyclones. In the absence of appropriate essential initiatives—vulnerability borders on the extreme. To increase their adaptability to cyclone disasters, all levels of society need to pay older persons special attention.